Performance of multi-layer steel fiber-reinforced mortar panels with air gaps against high-velocity bullets and successive firing - Apisit Techaphatthanakon; Buchit Maho; Sittisak Jamnam; Pochara Kruavit; Manote Sappakittipakorn; Phattharachai Pongsopha; Gritsada Sua-iam; Piti Sukontasukkul (Defence Technology)
This research addresses the growing demand for high-performance protective materials against high-velocity projectile impacts. The performance of multi-layered steel fiber-reinforced mortar (SFRM) panels with varying thicknesses and air gaps, was experimentally investigated under single and repeated impacts of 7.62×51 mm bullets fired from a distance of 50 m. The impact events were recorded using a high-speed camera at 40000 fps. Panel performance was assessed in terms of failure modes, kinetic energy absorption, spalling diameter, and percentage of back-face damage area, and weight loss. Results showed that panel configuration significantly influenced performance. Panel P10, with 70 mm SFRM thickness and 20 mm air gaps, provided the highest resistance, dissipating 5223 J of kinetic energy and preventing back-face damage. In contrast, P7, which absorbed 4476 J, presented a back damage area percentage of 8.93% after three impacts. Weight loss analysis further confirmed durability improvements, with P10 showing only 1.53% cumulative loss compared to 3.26% in P7. The inclusion of wider air gaps enhanced energy dissipation and reduced damage. Comparison between single and repeated impacts demonstrated the sustained resistance of high-performance panels, with P10 maintaining minimal degradation across three consecutive impacts. These findings highlight the potential of multi-layer SFRM panels to enhance ballistic resistance, making them suitable for military, security, and civilian protective applications requiring long-term durability.